Perturbations in elite female soccer matches: a conceptual and practical method to analyse variability and regularity between field zones and the spatial development of phase transitions - Marino, T. K.; Basso, L.; Morgans, R.; Cesar Corrêa, U.; Moreira, A. (International Journal of Performance Analysis in Sport, 2024)
In this study, perturbations in elite women`s soccer matches (UEFA Women`s Champions League 2021-2022) were examined. Their variability and regularity were determined considering field zones positioning. The perturbation actions were divided into single (one action only; SPA) and combined (two or more actions; CPA). From 266 perturbations, the "pass" was the most used action. The degree of centrality of the perturbation origin zones showed that zones 8 and 15 for SPA and, zones 8 and 9 for CPA were most the popular. Concerning destination zones, for SPA, zones 17 and 14 showed higher degrees and for CPA, zones 14 and 11. The coefficient of relative variability between the zones of origin (0.35) and destination (0.34) suggested a pattern of high variability. However, the relative coefficient of variability between the spatial development of the underlying phase transition highlighted relative predictability (0.19). In summary, the results suggest that elite women´s soccer players employ the pass action more frequently to change the stable state of the match. Additionally, it was observed high uncertainty regarding where, in terms of origin and destination zones, the underlying perturbation will occur. However, from one phase transition to the next, there is some regularity of the spatial development.